2020
DOI: 10.1080/26895293.2020.1817800
|View full text |Cite
|
Sign up to set email alerts
|

Impact of using low-cost packaging material of commercial herbal oil on its antibacterial compounds

Abstract: A commercial herbal oil with different bottle materials on the Indonesian markets was studied. The effects of the different specimens viz. PET-new, PET-open, and AL-new on the main antibacterial components of herbal oil were investigated.Step-1, analysis of antibacterial activity (against S. aureus and E. coli) and testing of non-toxic (in-vivo).Step-2, detection of the main antibacterial compounds (6 types) during the storage times. The market and environmental aspects were also considered. The results, all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
(30 reference statements)
0
2
1
Order By: Relevance
“…Unlike the tin (the previously analysed coffee packaging material), the plastic was predominantly evaluated as one-dimensional from the standpoint of ergonomic attributes. Plastic packaging can be more environmental-friendly compared to other packaging materials in some cases [38]. In contrast, our findings indicated that plastic as a packaging material was evaluated as less environmentally friendly, unlike glass.…”
Section: Materials Preferences For Cocoa Powder Packagingcontrasting
confidence: 63%
“…Unlike the tin (the previously analysed coffee packaging material), the plastic was predominantly evaluated as one-dimensional from the standpoint of ergonomic attributes. Plastic packaging can be more environmental-friendly compared to other packaging materials in some cases [38]. In contrast, our findings indicated that plastic as a packaging material was evaluated as less environmentally friendly, unlike glass.…”
Section: Materials Preferences For Cocoa Powder Packagingcontrasting
confidence: 63%
“…Researchers use qualitative descriptive research because the results are several descriptions or explanations sourced from human behavior, value systems, motivations, aspirations, and lifestyles. They are following the object to be studied by researchers (Susilo, 2010). This type of research is the primary data source used by researchers, namely the novel Al Karnak by Najib Mahfudz, which describes the social reality of Egyptian society in 1967 AD.…”
Section: Methodsmentioning
confidence: 99%
“…Meskipun keuangan keluarga merupakan salah satu sarana yang penting untuk memperlancar kegiatan perekonomian sehari-hari, namun masih banyak keluarga yang mengalami kesulitan dalam mengelola keuangan mereka (Susilo et al, 2014). Indonesia pada tahun 2021 menurut data asosiasi penyelenggara jasa internet indonesia.…”
Section: Pendahuluanunclassified